2019
DOI: 10.1002/mar.21181
|View full text |Cite
|
Sign up to set email alerts
|

The suffering company: Consumer compassion towards companies exposed to negative events

Abstract: When a company commits misconduct, it will usually suffer; for example, in the form of a short‐term decline in sales, a medium‐term loss of reputation, or a long‐term drop in its bottom line. But when a company is involved in a negative event for which it is fully responsible, for example, public customer agitations due to false expectations, some consumers might feel compassion for the company. In turn, they might aim to help the company overcome its period of suffering; for example, by making supportive reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 113 publications
(201 reference statements)
1
13
0
Order By: Relevance
“…They found that adjusted customer expectations strongly moderate the impact of customer satisfaction on repurchase behavior. Some of the theories explored in this cluster include social capital theory (Rey‐Moreno & Medina‐Molina, 2016), social identity theory (Hultman et al, 2019), and deservingness theory (Meyer et al, 2019), among others.…”
Section: Intellectual Structure Of Pandmmentioning
confidence: 99%
“…They found that adjusted customer expectations strongly moderate the impact of customer satisfaction on repurchase behavior. Some of the theories explored in this cluster include social capital theory (Rey‐Moreno & Medina‐Molina, 2016), social identity theory (Hultman et al, 2019), and deservingness theory (Meyer et al, 2019), among others.…”
Section: Intellectual Structure Of Pandmmentioning
confidence: 99%
“…Consumer compassion is a dynamic process in which emotional reactions are projected into the customer’s consciousness, particularly the consumer’s imagination about others’ experiences ( Meyer et al, 2019 ). Specifically, the consumer’s empathy consists of cognitive and emotional empathy.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…(Lastner et al, 2019). Another area it adds to is how consumers react to companies and their negative events (Meyer, Huber, & Huber, 2019). Though Meyer et al find some consumer compassion, here we uncover deeper sentiments of resistance.…”
Section: Daily Deal Details and Restrictionsmentioning
confidence: 56%
“…Furthermore, they add to the work on price perceptions and how there is a social element to the perception of buyer price deal fairness (Lastner et al, ). Another area it adds to is how consumers react to companies and their negative events (Meyer, Huber, & Huber, ). Though Meyer et al find some consumer compassion, here we uncover deeper sentiments of resistance.…”
Section: Discussionmentioning
confidence: 99%